POSTOPERATIVE COMPLICATIONS OF INTESTINAL ROTATION ABNORMALITIES IN CHILDREN (Herald of the National Children's Medical Center, 2024)
One of the causes of congenital intestinal obstruction is disorders of rotation and fixation of the middle intestine – intestinal malrotation (MC). According to the unanimous opinion of specialists, in case of MC, taking into account life-threatening complications, emergency or planned surgical treatment is indicated to establish a diagnosis. Despite the successes achieved in the surgical treatment of ICD, complications that occur intraoperatively and in the postoperative periods significantly worsen its results.